Correction: Magnetic properties of the seven-coordinated nanoporous framework material Co(bpy)1.5(NO3)2 (bpy = 4, 4′-bipyridine). Issue 25 (14th June 2018) - Bartolomé, Elena; Alonso, Pablo Javier; Arauzo, Ana; Luzón, Javier; Bartolomé, Juan; Racles, Carmen; Turta, Constantin
Abstract : Correction for 'Magnetic properties of the seven-coordinated nanoporous framework material Co(bpy)1.5 (NO3 )2 (bpy = 4, 4′-bipyridine)' by Elena Bartolomé et al., Dalton Trans., 2012, 41, 10382–10389.